A Soldier Reports - Westmoreland, William C., 1914-2005 (New York Boubleday & Comapny, 1976)
General Westmoreland traces his career from his cadet days at West Point through World War II and Korea, and concentrates on his years as commander of United States military forces in Vietnam.
Include Maps, Pictures and Index
Keywords: Vietnam War (1961-1975) -- Generals